Highly Dispersible Hexagonal Carbon–MoS2–Carbon Nanoplates with Hollow Sandwich Structures for Supercapacitors. Issue 18 (1st March 2019) - Quan, Ting; Goubard‐Bretesché, Nicolas; Härk, Eneli; Kochovski, Zdravko; Mei, Shilin; Pinna, Nicola; Ballauff, Matthias; Lu, Yan
Abstract: MoS2, a typical layered transition‐metal dichalcogenide, is promising as an electrode material in supercapacitors. However, its low electrical conductivity could lead to limited capacitance if applied in electrochemical devices. Herein, a new nanostructure composed of hollow carbon–MoS2 –carbon was successfully synthesized through anl ‐cysteine‐assisted hydrothermal method by using gibbsite as a template and polydopamine as a carbon precursor. After calcination and etching of the gibbsite template, uniform hollow platelets, which were made of a sandwich‐like assembly of partial graphitic carbon and two‐dimensional layered MoS2 flakes, were obtained. The platelets showed excellent dispersibility and stability in water, and good electrical conductivity due to carbon provided by the calcination of polydopamine coatings. The hollow nanoplate morphology of the material provided a high specific surface area of 543 m 2 g −1, a total pore volume of 0.677 cm 3 g −1, and fairly small mesopores (≈5.3 nm). The material was applied in a symmetric supercapacitor and exhibited a specific capacitance of 248 F g −1 (0.12 F cm −2 ) at a constant current density of 0.1 A g −1 ; thus suggesting that hollow carbon–MoS2 –carbon nanoplates are promising candidate materials for supercapacitors. Abstract : Made to stack : A new nanostructure composed of hollow carbon–MoS2 –carbon was successfully synthesized through anl ‐cysteine‐assisted hydrothermal method by using gibbsite as a template and polydopamine as a carbon precursor. Results show this is a promising electrode candidate for application in supercapacitors.